2011
DOI: 10.1155/2011/198737
|View full text |Cite
|
Sign up to set email alerts
|

Field Scale Studies on the Spatial Variability of Soil Quality Indicators in Washington State, USA

Abstract: Arable lands are needed for sustainable agricultural systems to support an ever-growing human population. Soil quality needs to be defined to assure that new land brought into crop production is sustainable. To evaluate soil quality, a number of soil attributes will need to be measured, evaluated, and integrated into a soil-quality index using the multivariable indicator kriging (MVIK) procedure. This study was conducted to determine the spatial variability and correlation of indicator parameters on a field sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Knowledge regarding the spatial distribution of soil enzyme activity across the landscape has great implications for interpreting the spatial pattern of OM decomposition and the rate of nutrient mineralization at regional scales [ 23 ]. When taking biological properties as the indicator of soil quality, it is necessary to consider the spatial variability of biological properties themselves as well as the underlying influencing factors [ 24 ]. Most studies have investigated the spatial variability of soil enzyme activities based on pot and/or microplot experiments [ 25 , 26 ], while few reports are available at regional scales [ 22 – 24 , 27 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge regarding the spatial distribution of soil enzyme activity across the landscape has great implications for interpreting the spatial pattern of OM decomposition and the rate of nutrient mineralization at regional scales [ 23 ]. When taking biological properties as the indicator of soil quality, it is necessary to consider the spatial variability of biological properties themselves as well as the underlying influencing factors [ 24 ]. Most studies have investigated the spatial variability of soil enzyme activities based on pot and/or microplot experiments [ 25 , 26 ], while few reports are available at regional scales [ 22 – 24 , 27 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…When taking biological properties as the indicator of soil quality, it is necessary to consider the spatial variability of biological properties themselves as well as the underlying influencing factors [ 24 ]. Most studies have investigated the spatial variability of soil enzyme activities based on pot and/or microplot experiments [ 25 , 26 ], while few reports are available at regional scales [ 22 – 24 , 27 29 ]. Because the experimental data are not always applicable to actual field conditions, it is necessary to carry out field studies on the spatial variability of soil enzyme activity, especially in arid and semiarid areas associated with serious soil erosion.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that a density of less than 1 sample per ha is able to capture the most variation in the predictors at farm scale (Debaene et al, 2014;Schmidt et al, 2014;Smith and Halvorson, 2011). Conditioned Latin hypercube sampling is a stratified random procedure that picks samples based on the distribution of predictors .…”
Section: Model Developmentmentioning
confidence: 99%
“…There were tried to select test indicators. Several soil biological indicators were rejected due to the high cost of analysis, so that it only used these indicators: organic matter, active carbon, potentially mineralizable of nitrogen, and root health rating [6]; lately, an increase in the use of soil microbial parameters has occurred [7].…”
Section: Introductionmentioning
confidence: 99%